OTIMIZAÇÃO DA SÍNTESE DE NANOPARTÍCULAS MAGNÉTICAS PARA EXTRAÇÃO DE ÁCIDOS NUCLEICOS - Ribeiro, Iuly Guimarães (2021)
Iron magnetic nanomaterials have been widely used in the field of biotechnology due to their ease of recovery and reuse of biological molecules with an external magnetic field. Although many works have reported promising applications with magnetic nanoparticles, a difficulty in controlling the synthesis almost always in the polydispersion of crystals and consequently in the lack of reproducibility of the experiments, directly impacting the scaling of many applications. Thus, this work aimed to optimize the synthetic of magnetic nanoparticles through a 5-1 fractional factorial design followed by a complete design 32 considering the main variables and previous levels already in the literature. A broad characterization was performed with the UVvis, MET, DLS, DRX, FTIR and Raman scattering techniques. Afterwards, the magnetic nanomaterials were functionalized with TEOS gain of colloidal stability and then with AMPTS to modify the positive surface. In addition, magnetic nanomaterials of Fe@SiO2@Ampts were recovered and nucleic acid purification compared to two commercially available techniques, namely the manual methodology with a silica column and the automated methodology with magnetic beads. The results of the application in the recovery of nucleic acids were obtained by RT-qPCR and interpreted by the Cq value (quantitation cycle). The optimized magnetic nanomaterials 12 nm average size, high stability and monodispersion. Regarding the application, the excellent Cq data that the magnetic nanomaterials optimized in this work have good reproducibility and efficiency in the recovery and purification of similar nucleic acids with the methodologies used commercially. Mainly due to the low cost and simplicity of production, these results indicate that the Fe@SiO2@Ampts NPMs produced in this work are a promising alternative for use in the recovery and purification of nucleic acids, in relation to commercial kits based on microspheres and column of silica by ultracentrifugation.